An Immunometabolic Shift Modulates Cytotoxic Lymphocyte Activation During Melanoma Progression in TRPA1 Channel Null Mice - Forni, Maria Fernanda; Domínguez-Amorocho, Omar Alberto; de Assis, Leonardo Vinícius Monteiro; Kinker, Gabriela Sarti; Moraes, Maria Nathalia; Castrucci, Ana Maria de Lauro; Câmara, Niels Olsen Saraiva (Frontiers in Oncology, 2021)
Melanoma skin cancer is extremely aggressive with increasing incidence and mortality. Among the emerging therapeutic targets in the treatment of cancer, the family of transient receptor potential channels (TRPs) has been reported as a possible pharmacological target. Specifically, the ankaryn subfamily, representing TRPA1 channels, can act as a pro-inflammatory hub. These channels have already been implicated in the control of intracellular metabolism in several cell models, but little is known about their role in immune cells, and how it could affect tumor progression in a process known as immune surveillance. Here, we investigated the participation of the TRPA1 channel in the immune response against melanoma tumor progression in a model of melanoma. Using TrpA1+ / + and TrpA1-/ - animals, we evaluated tumor progression using B16-F10 cells and assessed isolated T CD8+ cells for respiratory and cytotoxic functions. Tumor growth was significantly reduced in TrpA1-/- animals. We observed an increase in the frequency of circulating lymphocytes. Using a dataset of CD8+ T cells isolated from metastatic melanoma patients, we found that TRPA1 reduction is correlated with several immunological pathways. Naïve CD8+ T cells from TrpA1+/+ and TrpA1-/- animals showed different mitochondrial respiration and glycolysis profiles. However, under CD3/CD28 costimulatory conditions, the absence of TRPA1 led to an even more extensive metabolic shift, probably linked to an in vitro greater killing ability of TrpA1-/- CD8+ T cells. Therefore, these data demonstrate an unprecedented role of TRPA1 channel in the metabolism control of the immune system cells during carcinogenesis.